2017
DOI: 10.1097/bcr.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

Propylthiouracil-Associated Leukocytoclastic Necrotizing Cutaneous Vasculitis

Abstract: The purpose of this case report and review of the literature is to provide an exploration of the clinical symptoms, diagnosis, prevention, and management of propylthiouracil (PTU)-associated vasculitis in the intensive care setting. A PubMed search of the available literature was conducted using the MeSH search terms "propylthiouracil" and "vasculitis." The literature search returned 121 articles. Twenty-five were excluded because they were not in English. Fifty-nine case reports or case studies describing PTU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…Namely, Lee et al reported a case of LCV caused by another anti-cancer drug, everolimus. The patient presented with no systemic manifestations of vasculitis and did not receive any immunosuppressive therapy, but he needed skin grafting [4]. Our colleagues Grasic et al presented a similar case with everolimus connected to LCV, where the patient needed only treatment discontinuation and local measures, as in our case [7].…”
Section: Fig 4 Skin Lesions Three Months After the 1st Presentation (September 2018)mentioning
confidence: 68%
See 1 more Smart Citation
“…Namely, Lee et al reported a case of LCV caused by another anti-cancer drug, everolimus. The patient presented with no systemic manifestations of vasculitis and did not receive any immunosuppressive therapy, but he needed skin grafting [4]. Our colleagues Grasic et al presented a similar case with everolimus connected to LCV, where the patient needed only treatment discontinuation and local measures, as in our case [7].…”
Section: Fig 4 Skin Lesions Three Months After the 1st Presentation (September 2018)mentioning
confidence: 68%
“…Leukocytoclastic vasculitis is a histopathological term used to describe a variety of types of small vessel vasculitis and mainly refers to the skin, although there are types of vasculitis that can affect other regions of the body. By using the positive results from direct immunofluorescence examination, we may categorize the type of LCV based on the detection of immune complex deposits in the vessel wall [2,4]. LCV presents approximately seven to ten days after exposure to the causative agent.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, like in our patient, further immunosuppression is required. Late presentation can be life‐threatening …”
Section: Discussionmentioning
confidence: 99%
“…PTU vasculitis occurs more commonly in females, and the most common symptoms are rash, fever and arthralgia . It can affect any organ system.…”
Section: Discussionmentioning
confidence: 99%
“…Usually it is limited to the skin in a form of cutaneous leukocytoclastic vasculitis, but may also affect organs including kidneys and lungs. Some fatal cases have been reported even with limited cutaneous disease [11]. Discontinuation of PTU should be a first step in the treatment and could lead to complete resolution of symptoms.…”
Section: Discussionmentioning
confidence: 99%